WHEAT STRAW OPTIMIZATION VIA ITS EFFICIENT PRETREATMENT FOR IMPROVED BIOGAS PRODUCTION - Memon, Muhammad Jaffar; Memon, Abdul Rehman (Civil Engineering Journal, 2020)
The complex indigenous configuration of non-bio-labile wheat straw necessitates its pretreatment to optimize the breakdown of its structural components for its ultimate conversion into biogas by means of anaerobic digestion. In this research work, wheat straw was pretreated with potassium hydroxide (KOH) to facilitate its improved biodegradability. The pretreatment of wheat straw was also obvious in terms of its crystallinity resulting in the improved amorphous regions compared to the control wheat straw. The results showed that pretreated wheat straw digestion transpired into comparatively higher removal of TS (86%), VS (89%) and total lignin, cellulose and hemicellulose (22%) than that obtained with control wheat straw. Maximum biogas production accrued was 1550 mLN per day with optimized dosing of KOH compared to 967 mLN per day obtained with control wheat straw, implying that the cumulative biogas production was improved by 45% using pretreated wheat straw than that using control wheat straw. These results suggested that pretreated wheat straw digestion led to a significant improvement in the biogas yield.